The Dynamics of Entrepreneurship Education in Higher Education: The Role of Family Background and Environment in Developing Entrepreneurial Skills - Alfattory Rheza Syahrul; Suryana Suryana; Heny Hendrayati; Chairul Furqon (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This study aims to investigate the influence of entrepreneurship education at the university level on the development of students’ entrepreneurial skills, with a particular focus on the potential moderating role of entrepreneurial family background. As entrepreneurship education becomes increasingly prioritized in higher education, understanding how familial entrepreneurial exposure interacts with formal education is crucial for shaping effective curricula. Methodology: Quantitative research approach was adopted, using descriptive and inferential statistical analysis. The study involved a sample of 189 university students in Padang, selected through purposive sampling. Data were collected through a validated Likert-scale questionnaire measuring students’ experiences with entrepreneurship education, entrepreneurial skills development, and family background characteristics. The analysis was conducted using SmartPLS to explore both direct and moderating effects. Main Findings: The results revealed that entrepreneurship education has a significant positive impact on students’ entrepreneurial skills development. Surprisingly, students’ entrepreneurial family background did not exert a direct influence nor moderate the relationship between education and skills acquisition. The findings emphasize that while family background may offer exposure, formal entrepreneurial training is critical for equipping students with practical and theoretical competencies. Furthermore, a supportive academic environment emerged as a key factor in enhancing students’ entrepreneurial capabilities. Novelty/Originality of this Study: This study introduces a new perspective by exploring the often-overlooked moderating role of family background in the Indonesian context. It offers empirical evidence that challenges assumptions about the primacy of family influence, reinforcing the necessity of structured entrepreneurship education to nurture future entrepreneurs in diverse socio-cultural settings.